Social Media as a Tool for Disseminating Scientific Knowledge on Child Abuse and Resilience: A Brazilian Experience - Souza, Francine; Goldfarb, Deborah; Priolo Filho, Sidnei Rinaldo (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2023)
Objectives: Social media is a common tool for disseminating information in developing countries, including Brazil. Research regarding social media’s effect on increasing awareness of and knowledge about child abuse has yet to be widely tested in those countries. This exploratory study tested whether social media is a viable outlet for disseminating empirically supported information about child abuse in Brazil.Methods: We utilized social media platforms, such as Facebook, ResearchGate, Twitter (which has subsequently rebranded as X but will be referred to herein as Twitter), Instagram, and YouTube, to disseminate a series of short videos, in cartoon format, on the scientific research surrounding child abuse, adverse childhood events, and resiliency to such experiences.Results: The results indicate that social media has a promising reach in Brazil, as the dissemination started by 10 researchers had over 30,000 views.Conclusion and Implications: Social media may be a viable format for disseminating empirically-supported information in developing countries like Brazil. Each platform, however, has its own characteristics and, as such, the target audiences, engagement, delivery, followers, impact time, and other metrics vary across platforms. Additionally, not all social media platforms provide the same outreach internationally. Future directions are discussed.